No home bias in ghost games - Dilger, A.; Vischer, L. (University of Münster, Institute for Organisational Economics, 2020)
Because of the COVID-19-pandemic the men's first German football league (Bundesliga) had to finish the season 2019/20 with ghost games as spectators were not allowed in the stadiums. Comparing these games with the regular ones between the same teams before, we find that the normal advantage for the home team disappears. One reason for this is the disappearances of the home bias of the referees whereas changes in the sportive performance of the teams seem to be irrelevant in this regard.